If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 12x + -6 + -7x Reorder the terms: 9 = -6 + 12x + -7x Combine like terms: 12x + -7x = 5x 9 = -6 + 5x Solving 9 = -6 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 9 + -5x = -6 + 5x + -5x Combine like terms: 5x + -5x = 0 9 + -5x = -6 + 0 9 + -5x = -6 Add '-9' to each side of the equation. 9 + -9 + -5x = -6 + -9 Combine like terms: 9 + -9 = 0 0 + -5x = -6 + -9 -5x = -6 + -9 Combine like terms: -6 + -9 = -15 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| n^2-2n=11 | | x^(2/3)=9 | | Y=sin(16x) | | x+2x=45600 | | F(x)=3/4x-5 | | ln(x+3)+ln(x+5)=0 | | 4m+4m-8m+m=9 | | .3a=14 | | 5-3(2X-4)=29 | | 2y+13= | | (1/2)(sqr3/2) | | 8x^4+16x^3-12x^2+4x= | | D=10+7 | | 2(sqr3/2) | | 8w^2=32 | | 14h-3h+-17h=18 | | 5m^2=125 | | -7(1-8a)+5a=-7+5a | | 8x-6+5x+12=180 | | 7y-2(3-1)=8 | | 28-8x=-1211x | | 2n+3.6=6.4whatisn | | ln(x^2+4x-5)-ln(x+5)=1 | | (8-x)+(3-x)=11 | | 5t^4-25t^2-20=0 | | 9x-2=10x-9 | | 127+2x+41=180 | | 5t^2-25t+20=0 | | (69.8+x)/7=70 | | 6n+3.30=7.80 | | a=4+1.5y | | 4(2x+1)-x=10 |